Government and public policy in the Pacific Islands - Hassall, Graham (Emerald Publishing Limited, 2020)
The first comprehensive examination of how systems of government have emerged in the small and diverse developing island states of the Pacific Islands region, this study outlines the way in which government systems in the region have evolved from their pre-independence origins to their current political, constitutional, and public sector arrangements. Drawing on scholarship from the fields of law, history, anthropology, public policy, and public management, the author examines the ways in which culture, history, and the environment continue to influence contemporary policy challenges and policy processes in these states. Recognising the significant challenges that small states face in terms of human and economic development, as well as how they must navigate between autonomy and self-reliance in some sectors, yet supra-national collaboration in others, the author argues that the future prosperity of the Pacific Islands region and the countries within it is not yet assured. Their economies struggle to keep pace with population growth and public aspirations, and service delivery in key sectors is often inadequate. Indeed, the fundamental challenge facing the Pacific Islands' leaders and governments is ensuring the adoption of policies and methods of implementation that, ultimately, pave the way for their continued development within the emerging global order.
Chapter 1: Pacific Islands life worlds -- Chapter 2: Government Systems -- Chapter 3: Governance and Public Policy: the interaction of systems and life worlds.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Oceania -- Politics and government; Policy sciences -- Oceania; Political Science -- Public Policy -- General; Public administration